Screen-Viewing Behaviors Among Preschoolers: Parents’ Perceptions - He, Meizi (Am J Prev Med, 2005)
BACKGROUND: Childhood obesity has emerged as a public health concern in Canada. It has been suggested that excessive screen viewing (i.e., television, computer, video) is a major factor contributing to the increased risk of obesity in children. Exploring young children’s experiences with this modifiable behavior may be beneficial to the creation of a multifaceted program aimed at the primary prevention of obesity. OBJECTIVES: To seek parents’ perceptions and insights pertaining to their preschoolers’ screen-viewing behaviors. METHODS: This qualitative study targeted a heterogeneous sample of parents with children aged 2.5 to 5 years. Two experienced moderators using a semistructured interview guide conducted the ten focus groups between September and November 2003. All focus groups were audio-recorded and transcribed verbatim. In fall 2003 to spring 2004, inductive content analysis was conducted independently by a minimum of two qualitative researchers. RESULTS: Many parents were not concerned with the amount of screen viewing their children engaged in, although the content of what was on the screen was of particular interest to them. Very few parents seemed to appreciate the linkage between preschoolers’ screen-viewing habits and their potential risk for obesity. CONCLUSIONS: Public health interventions are needed to increase parents’ awareness with respect to the harmful effects of excessive screen viewing in preschoolers.